Oxygen and hydrogen photocatalysis by two-electron mixed-valence coordination compounds - Bachmann, Julien; et al. (Coordination Chemistry Reviews, 2005)
Two-electron mixed valency is a useful design concept for hydrogen and oxygen photocatalysis. As single-electron mixed-valence compounds react in one-electron steps, two-electron mixed-valence compounds may react in two-electron steps at the constituent redox sites, whether they are metal- or ligand-based. With the redox centers working in concert upon photoexcitation, two- and four-electron transformations are promoted along excited-state pathways. Such a strategy is ideally suited to the activation of small molecules. We describe the photochemistry for hydrogen and oxygen activation using two-electron mixed-valence complexes of three different motifs: (a) M-n-Mn+2 bimetallic complexes, (b) tetrapyrrole macrocycles and (c) externally bridged di-iron(III) mu-oxo porphyrin dimers. (c) 2005 Elsevier B.V. All rights reserved.
Keywords: hydrogen; oxygen; photocatalysis; valence; multielectron; solar; proton-coupled electron transfer